1996
DOI: 10.1017/s0031182000065021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis ofGiardia intestinalisisolates at the glutamate dehydrogenase locus

Abstract: SUMMARYSamples of DNA from a panel ofGiardiaisolated from humans and animals in Europe and shown previously to consist of 2 major genotypes–‘Polish’ and ‘Belgian’–have been compared with human-derived Australian isolates chosen to represent distinct genotypes (genetic groups I–IV) defined previously by allozymic analysis. Homologous 0·52 kilobase (kb) segments of 2 trophozoite surface protein genes (tsa417 and tsp11, both present in isolates belonging to genetic groups I and II) and a 1·2 kb segment of the glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 47 publications
5
103
0
4
Order By: Relevance
“…The only two previous studies, which analysed a small number of Giardia isolates from Queensland, identified both assemblage A and B (Nolan et al 2011;Ebner et al 2015). Analysis of genetic variability within assemblages has shown that isolates of assemblage A can be divided into four sub-assemblages (AI, AII, AIII and AIV) by protein polymorphisms of 23 loci (Monis et al 1996(Monis et al , 2003, with human isolates belonging to AI and AII and animal isolates belonged to AI, AIII and AIV (Monis et al 2003;Cacciò et al 2008;Sprong et al 2009;Ryan and Cacciò, 2013). In the present study, although there was 100% concordance between loci in assignment to assemblage, there were some differences in assignment to sub-assemblage level.…”
Section: Discussionmentioning
confidence: 99%
“…The only two previous studies, which analysed a small number of Giardia isolates from Queensland, identified both assemblage A and B (Nolan et al 2011;Ebner et al 2015). Analysis of genetic variability within assemblages has shown that isolates of assemblage A can be divided into four sub-assemblages (AI, AII, AIII and AIV) by protein polymorphisms of 23 loci (Monis et al 1996(Monis et al , 2003, with human isolates belonging to AI and AII and animal isolates belonged to AI, AIII and AIV (Monis et al 2003;Cacciò et al 2008;Sprong et al 2009;Ryan and Cacciò, 2013). In the present study, although there was 100% concordance between loci in assignment to assemblage, there were some differences in assignment to sub-assemblage level.…”
Section: Discussionmentioning
confidence: 99%
“…The typical applications of these loci have therefore varied accordingly. For Giardia the conserved SSU rDNA is traditionally used for species and assemblage/subassemblage level genotyping (Sogin et al 1989 ;van Keulen et al 1991van Keulen et al , 1993van Keulen et al , 1995Hopkins et al 1997), where as the most variable locus, tpi, is frequently used for subtyping clinical samples (Lu et al 1998 ;Amar et al 2002) and the gdh locus, with a substitution rate midway between them, has a broad application spectrum (Monis et al 1996(Monis et al , 1999.…”
Section: Consensus Sequence Substitutionsmentioning
confidence: 99%
“…(1) Thompson et al (2000), (2) Sogin et al (1989), (3) van Keulen et al (1995), (4) Not yet published, Xiao, S., South China Agricultural University, 2005, (5) Healey et al (1990), (6) , (7) Monis et al (1999), (8) (2000), (20) Yee and Dennis (1992), (21) Ey et al (1997), (22) Leonhard et al (2006), (23) Monis et al (1996), (24) Ey, P., University of Adelaide, 2002, submitted as a set with those from Ey et al (1997), (25) , (26) Itagaki et al (2005), (27) Matsubayashi et al (2005), (28) Robertson et al (2006), (29) Mowatt et al (1994), (30) Trout et al (2003), (31) Baruch et al (1996), (32) Sulaiman et al (2003), (33) Sulaiman et al (2004), (34) Not yet published, Mowatt, M., National…”
mentioning
confidence: 99%
“…Infection occurs by faecal oral route transmission, either by direct contact or by ingestion of contaminated food or water (Monis and Thompson, 2003). Despite morphological uniformity, considerable biotypic and genetic diversity exists within the G. duodenalis species (Monis et al, 1996 andThompson et al, 2000). The species includes several 'assemblages' or genotypes, A-G, that can be discriminated on the basis of host selection and genomic mutations (Monis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%